2012
DOI: 10.3109/19401736.2012.731400
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation ofOmpok bimaculatus(Teleostei: Siluridae) population based on mtDNA cytochromebgene

Abstract: Ompok bimaculatus commonly called as Indian butter catfish is a commercially important food fish and distributed throughout India and Southeast Asia. Genetic differentiation of O. bimaculatus was investigated using cytochrome b (cyt b) gene of three different riverine populations. A total of 37 sequences of cyt b gene (1118 bp) were generated from O. bimaculatus. The mitochondrial DNA analysis revealed that O. bimaculatus has relatively high genetic diversity. The estimated haplotype and nucleotide diversity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In this study we have not yet determined genetic variation of O. bimaculatus, but previous studies have revealed genetic differentiation levels suggesting very limited gene flow among populations (Malakar et al, 2013). Biological effects and/ or unsustainable fishing practices may lead to a modification of their reproductive strategies: decreasing their L50 and increasing their reproduction effort (Kovacic, 2004;Perera-Garcia et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In this study we have not yet determined genetic variation of O. bimaculatus, but previous studies have revealed genetic differentiation levels suggesting very limited gene flow among populations (Malakar et al, 2013). Biological effects and/ or unsustainable fishing practices may lead to a modification of their reproductive strategies: decreasing their L50 and increasing their reproduction effort (Kovacic, 2004;Perera-Garcia et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…The differences in reproductive potential of O. bimaculatus among different populations may reflect environmentally induced phenotypic plasticity and /or genetic variations (Gueye et al, 2012). In a recent study, Malakar et al (2013) reported relatively high genetic diversity of O. bimaculatus using cyt-b gene of three different riverine populations of O. bimaculatus. It can be predicted, therefore, that the O bimaculatus populations studied here and showing high variations in reproductive traits are genetically distinct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low G values are commonly found in the mitochondrial DNA of the Iberian Barbels fishes (Doadrio et al 2002) and Glyptosternoid fishes (Peng et al 2004). This lower G value is also found in O. bimaculatus (Malakar et al 2013). The pattern of differences between A, T, C, and G can show genetic signs and characteristics of a species (Afreixo et al 2009).…”
Section: Resultsmentioning
confidence: 91%
“…The cytochrome b gene contains the position of codons that develop slowly and rapidly, as well as more intraspecific variations, especially in the third position of codons that can be used to identify stocks (Habib et al 2011). Therefore, this gene has been used for a diversity of systematic questions (Malakar et al 2013). In this study, the mitochondrial cytochrome b gene region (906 base pairs) was used for genetic markers of 14 individuals from four species from three genera of silurid catfishes in the Kampar River, Indonesia.…”
Section: Introductionmentioning
confidence: 99%